The Double Dynamic Martin Screw (DMS) Adjustable Implant System for Proximal and Distal Femur Fractures - Dittel, Karl-Klaus.; Rapp, Matthias; SpringerLink (Online service) (Heidelberg : Steinkopff : Imprint: Steinkopff, 2008)
The scope and importance of hip fractures is almost incomprehensible. With a world wide incidence of close to 2 million cases per year, theses fractures pose a daunting challenge to our ability to affect and treat this epidemic. Basics for operative treatment of proximal and distal femur fractures: Clear surgical indication Short planning and preparation < 24 h Full weight bearing osteosynthesis Early mobilisation and physiotherapy In comprehensive form the book presents the usage of a meanwhile well installed implant (DMS) for osteosynthesis technique in the peritrochanteric region. The „double dynamic" stabilization (sliding tongue principle and angle adapted contoured fit) means a state of the art fracture treatment procedure. It is a convincing alternative to achieve a biological osteosynthesis at the femur. The system includes an infinitely adjustable, flexible angle, dynamic plate with a tubular distal part.
Conventional hip surgery in traumatology -- A century of experiments and experiences -- Technical properties of the DMS -- The analysis of hip compression screws made of implant steel under static and limit load requirements -- Implants and instruments -- Radioanatomy -- Abnormal radiographic anatomy of the proximal femur -- Fracture classification at the proximal femur -- Statistical items -- Surgical technique for fracture treatment -- Operative procedure -- Operative procedures (Case reports) -- The prognosis of the femur neck fracture after headpreserving osteosynthesis -- Intermediate DMS (2/3 implant) -- Stabilization of intertrochanteric fractures with the Dynamic Martin Screw (DMS) -- The 31A 3-3 fracture: an unstable problem -- Subtrochanteric femur and proximal femur shaft fractures -- Application of the Dynamic Martin Screw (DMS) in the intertrochanteric osteotomy -- Distal femur fractures -- Pathologic fractures and osteolyses at the femur -- The use of an innovative femur neck prosthesis in case of complications after hip fracture surgery -- Exceptional indications -- Additional and adjuvant measurements and procedures -- Systemic antibiotics in the prophylaxis and therapy of postoperative infections in patients with osteosynthesis of the femur -- Prevention of venous thromboembolism in hip surgery -- Physiotherapy after surgery for proximal femur fractures -- Operative revisional management -- Evidence-based drug treatment of osteoporosis -- Closing remarks.
Keywords: Orthopedics; Surgical Orthopedics; Orthopedics